2014
DOI: 10.1666/13-092
|View full text |Cite
|
Sign up to set email alerts
|

X-ray computed tomography of two mammoth calf mummies

Abstract: Two female woolly mammoth neonates from permafrost in the Siberian Arctic are the most complete mammoth specimens known. Lyuba, found on the Yamal Peninsula, and Khroma, from northernmost Yakutia, died at ages of approximately one and two months, respectively. Both specimens were CT-scanned, yielding detailed information on the stage of development of their dentition and skeleton and insight into conditions associated with death. Both mammoths died after aspirating mud. Khroma's body was frozen soon after deat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0
1

Year Published

2015
2015
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 31 publications
2
21
0
1
Order By: Relevance
“…2). This morphology exactly mirrors the juvenile morphology of the endocast in young elephants (Shoshani et al, 2006), in the young mammoth Khroma (Fisher et al, 2014), and in its supposed ancestor P. antiquus (Accordi and Palombo, 1971;Palombo, 2001;Palombo and Giovinazzo, 2005). These last authors also showed that the endocranial cavity grew following an intraspecific allometric scaling, resulting in a large endocranial volume with respect to body mass.…”
Section: Insular Dwarfism and Brain Size Scalingsupporting
confidence: 70%
See 2 more Smart Citations
“…2). This morphology exactly mirrors the juvenile morphology of the endocast in young elephants (Shoshani et al, 2006), in the young mammoth Khroma (Fisher et al, 2014), and in its supposed ancestor P. antiquus (Accordi and Palombo, 1971;Palombo, 2001;Palombo and Giovinazzo, 2005). These last authors also showed that the endocranial cavity grew following an intraspecific allometric scaling, resulting in a large endocranial volume with respect to body mass.…”
Section: Insular Dwarfism and Brain Size Scalingsupporting
confidence: 70%
“…Methods used by previous authors to estimate CC are detailed in the caption of Table 2. Notably, before this study, no estimation of CC has ever been made for an adult Mammuthus primigenius (the CC of the frozen mammoth calf Khroma approximates 2300 cm 3 ; Fisher et al, 2014). Therefore, the double graphic integration method of Jerison (1973) was used to estimate CC from figures of the endocast in dorsal and lateral views, including olfactory bulbs, in Simionescu and Morosan (1937).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent examples of the use of virtual palaeontology techniques in the study of proboscideans investigate a variety of issues ranging from osteology (Fisher et al, 2014a) to ontogeny and taphonomy (Fisher et al, 2014b), and even dentin density changes in annual increments (Cherney et al, 2014;El Adli et al, 2014) with the use of X-ray tomography.…”
Section: Discussionmentioning
confidence: 99%
“…The age determination given by Roth and Shoshani (1988) shows that a three-dayold Asian elephant could have two plates worn on the DP2, but the DP3 was not erupted yet. Among the specimens of M. primigenius, Lyuba's dentition consists of fully formed and almost-erupted deciduous tusks (DI2), fully formed and justerupted DP2s, and incompletely formed and unerupted dP3s and dP4s , Kosintsev et al (2010) refer to her age as "no older than two or three months", and Rountrey et al (2012) and Fisher et al (2014) offered a more precise determination of about one month, based on discovery of a neonatal line in her dentin, marking the time of birth, and postnatal dentin increments in her dP2s.…”
Section: Determination Of Age At Time Of Deathmentioning
confidence: 99%